Smear layer removal capacity of disinfectant solutions used with and without EDTA for the irrigation of canals: a SEM study. - Menezes, Ana Carolina Silveira Cardoso de; Zanet, Caio Gorgulho; Valera, Márcia Carneiro (My University, 2003)
The purpose of this study was to carry out a scanning electron microscopic (SEM) analysis of the cleaning qualities and smear layer removal from root canal walls, instrumented and irrigated with 2.5% NaOCl, 2.0% chlorhexidine and saline solutions. Fifty extracted teeth were used in this study. All teeth were radiographed to determine the existence of a single canal. The crowns were cut at the cervical limit and the root canals were instrumented with K-type files up to size 45. During root canal preparation, irrigations were made with the different solutions being evaluated: Group 1: 2.5% NaOCl (10 roots); Group 2: 2.5% NaOCl and 17% EDTA for 2 minute (10 roots); Group 3: 2.0% chlorhexidine (10 roots); Group 4: 2.0% chlorhexidine and 17% EDTA for 2 minutes (10 roots); Group 5: saline solution (5 roots); Group 6: saline solution and 17% EDTA for 2 minutes (5 roots). After instrumentation, the canals were irrigated with each one of the solutions and the roots were cut in the buccolingual direction for SEM analysis, at the cervical, middle and apical thirds, to ascertain the presence or absence of smear layer and debris. SEM analysis was performed by three calibrated examiners and scores were submitted to Kruskal-Wallis test at the significance level of p = 5%. Results showed that the use of 17% EDTA decreased the smear layer significantly (p < 0.05) for all evaluated solutions in all thirds. When EDTA was not used, a significantly higher quantity of smear layer on the apical third was observed only in the NaOCl groups. The use of 17% EDTA was significant for debris removal except for the chlorhexidine groups. The following conclusion could be drawn: the use of 17% EDTA was necessary to enhance cleanness of the root canals.
Keywords: biomedical and dental materials; chelating agent; chlorhexidine; edetic acid; hypochlorite sodium; topical antiinfective agent; analysis of variance; dental surgery; drug effect; human; nonparametric test; scanning electron microscopy; tooth pulp; ultrastructure; Analysis of Variance; Anti-Infective Agents, Local; Chelating Agents; Chlorhexidine; Dental Pulp Cavity; Edetic Acid; Humans; Microscopy, Electron, Scanning; Root Canal Irrigants; Smear Layer; Sodium Hypochlorite; Statistics, Nonparametric